Two-year process evaluation of a pilot program to increase elementary children's physical activity during school. (April 2018) - Webster, Collin A.; Weaver, R. Glenn; Egan, Cate A.; Brian, Ali; Vazou, Spyridoula
Highlights: A classroom movement integration (MI) pilot intervention was evaluated. Systematic observations showed no changes in the extent MI. Interviews indicated teachers liked the intervention but still faced MI challenges. A more thorough evaluation schedule may be needed to fully capture MI instances. Abstract: The purpose of this study was to examine implementation processes in elementary classrooms during a 2-year (Fall 2014 to Spring 2016) pilot intervention program, Partnerships for Active Children in Elementary Schools (PACES). We examined (a) the effect of PACES on the extent of movement integration (MI) and (b) changes in teachers' perceptions regarding MI. Purposively selected classrooms (grades 1–3) across four schools (3 intervention, 1 control) participated in the study. The sample included classroom teachers (N = 12) in Fall 2014 and Spring 2015, but the number of participants dropped to eight in Fall 2015 and Spring 2016. PACES consisted of three partnership approaches (a virtual community of practice, community-based participatory research, and university service learning) intended to increase the extent of MI in the intervention classrooms. We collected process data using the System for Observing Student Movement in Academic Routines and Transitions (SOSMART) and teacher interviews. PACES did not significantly impact the extent of observed MI. Interviews indicated that the intervention had both strengths and limitations. Building interpersonal support for teachers is important to their use of MI. A different measurement schedule (e.g., collecting MI data each day of the school week) may be required to more thoroughly capture MI instances.